Geography, climate, ecology: What is more important in determining bee diversity in the Aegean Archipelago?. (9th October 2018) - Kaloveloni, Aggeliki; Tscheulin, Thomas; Petanidou, Theodora
Abstract: Aim: Understanding which factors drive α‐ and β‐diversity is fundamental to ecological and biogeographical research. Especially in archipelagos, diversity patterns are interesting due to the numerous factors influencing them. Here, we investigate the importance of climate and ecogeographical factors in shaping α‐ and β‐diversity patterns of bee species in the Aegean Archipelago, a bee diversity hotspot. Location: Nineteen islands in the Aegean Archipelago, located along a N–S climate gradient. Methods: We systematically sampled the bee fauna of phryganic communities in 100 sites across 19 islands. Using generalized linear models (GLMs), we tested climatic (viz. annual mean temperature and annual precipitation), geographical (island area, proportion of surrounding land mass, distance to climatically similar land mass, and maximum step length of pathway to nearest island/mainland), and ecological parameters (viz. floral abundance) as determinants of bee diversity. Following a multimodel island species–area relationship (ISAR) framework, we ranked islands according to the observed richness to identify biodiversity hotspots. Furthermore, we estimated the effect of the above factors on overall β‐diversity as well as on turnover and nestedness components, using multiple regression models on distance matrices. Results: Island area was the best predictor, positively affecting α‐diversity, together with precipitation, surrounding land mass proportion, and floral abundance. Temperature was found to have a significant negative effect on α‐diversity. Among all study islands, Samothraki and Kea stood out as bee diversity hotspots, with a bee richness higher than predicted by the multimodel ISAR. The overall β‐diversity was mainly driven by the turnover component and positively related to precipitation differences, whereas the nestedness component was positively affected by differences in area and surrounding land mass proportion. Main conclusion: This study highlights the importance of geography and climate in shaping both α‐ and β‐diversity of bees in the Aegean and suggests that both factors are likely to be crucial for analysing and predicting bee diversity responses to future environmental changes.